Wittgenstein: From Ethics to Blind Rule-Following and Back Again - Nowak, Ewa (ETHICS IN PROGRESS, 2019)
The paper discusses Wittgenstein’s approaches to ethics within two contrastive contexts, e.g., pragmatism and cooperative-discursive normative practice. The first section revisits the fiasco of his early “negative” ethics. The second section subsequently shows how Wittgenstein’s mature concept of blind rule-following displaces normativity but simultaneously becomes the key predictor for discourse ethics (or, rather, a specific kind of it). The final section discusses the pros and cons of finitism in the light of contemporary philosophy of mind. As a conclusion, the author provides evidence for her hypothesis that there is no normative (embodied) mind without a manifest normative competence, which includes moral judgment and discursive competence.